2020
DOI: 10.1093/nargab/lqaa048
|View full text |Cite
|
Sign up to set email alerts
|

Development of multiepitope subunit protein vaccines against Toxoplasma gondii using an immunoinformatics approach

Abstract: Abstract Approximately one-third of the world’s human population is estimated to have been exposed to the parasite Toxoplasma gondii. Its prevalence is reportedly high in Ethiopia (74.80%) and Zimbabwe (68.58%), and is 40.40% in Nigeria. The adverse effect of this parasite includes a serious congenital disease in the developing fetus of pregnant women. After several efforts to eliminate the disease, only one licensed vaccine ‘Toxovax’ has been used to avoid conge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…The addition of T. gondii profilin to the vaccine serves a crucial role since profilin is a protein known to function as a critical ligand recognised by receptors such as TLR11 and TLR2, crucial for activating host immune response via Th1 adaptive response during a parasite-host invasion [2] . Adding these linkers and an adjuvant to the vaccine construct aided in the flexibility and improved stability of the tertiary structure or model of the proposed vaccine, while the adjuvant enhanced the immunogenicity of the designed vaccine [22] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of T. gondii profilin to the vaccine serves a crucial role since profilin is a protein known to function as a critical ligand recognised by receptors such as TLR11 and TLR2, crucial for activating host immune response via Th1 adaptive response during a parasite-host invasion [2] . Adding these linkers and an adjuvant to the vaccine construct aided in the flexibility and improved stability of the tertiary structure or model of the proposed vaccine, while the adjuvant enhanced the immunogenicity of the designed vaccine [22] .…”
Section: Methodsmentioning
confidence: 99%
“…Various research has focused on different antigens found in the parasite to develop a peptide-based vaccine against T. gondii , namely, dense granule proteins, microneme proteins, rhoptry proteins and surface antigens and apical membrane antigens [17] , [18] , [19] , [20] . Research works focusing on T. gondii antigens as alternative control strategies through vaccination have been previously implemented, verifying the importance of improved control measures to alleviate toxoplasmosis [17] , [21] , [22] , [23] , [24] .…”
Section: Introductionmentioning
confidence: 99%
“…The subunit vaccines with multiple epitope designs are more valuable for research. Onile et al used immune informatics tools to design multi-epitope subunit vaccines with different T-cell and B-cell epitopes to fight toxoplasmosis 14 . Two recombinant proteins, recombinant rhoptry protein 18 (rROP18) and recombinant calcium-dependent protein kinase 6 (rCDPK6), combined with Poly (lactide-co-glycolide) (PLG), a biodegradable and biocompatible polymer, prolong the protein release period, lower protein degradation and induce a long-lasting immune response.…”
Section: Anti- T Gondii Vaccinesmentioning
confidence: 99%
“…Currently, multi-epitope vaccines have been designed against many pathogenic microorganisms, including Shigella spp. [19] , foot-and-mouth disease virus [20] , Helicobacter pylori [21] , [22] , hepatitis B virus [23] , Toxoplasma gondii [24] , Leishmania infantum [25] , Nipah virus [26] , Onchocerca volvulus [27] , Pseudomonas aeruginosa [28] , and leukosis virus [29] . In particular, the emergence of the COVID-19 pandemic has strengthened the application of this technology [16] , [30] , [31] , [32] .…”
Section: Introductionmentioning
confidence: 99%